Reproduction of intra-radicular surface anatomy of extracted human teeth: comparison of three different materials using injection technique - Sultana, A; Rahman, MM; Rahman, MM; Shrestha, P (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Jul;19(2):181-4. The abstract of this article is available on the PubMed website